Preschoolers' and Adults' Animism Tendencies Toward a Humanoid Robot - Okanda, M; Taniguchi, K; Wang, Y; Itakura, S (Elsevier, 2021)
This study examined whether three- and five-year-old children and adults changed their perceptions of a robot after a naturalistic interaction with it. We examined whether participants exhibited animism errors (i.e., attributing biological properties to a target in addition to psychological, perceptual, and name properties) or agentic animism (i.e., attributing psychological, perceptual, name, and artifact properties to a target while not attributing biological properties) before and after they interacted with the robot. Results indicated that the three-year-olds made animism errors: they were more likely than older participants to attribute biological properties to the robot, although this tendency decreased after the interaction. The five-year-olds and adults did not attribute biological properties to the robot before or after the interaction, suggesting that they did not make animism errors. Additionally, the five-year-olds attributed more perceptual properties to the robot after the interaction and the adults showed a similar, yet modest tendency. Thus, older participants tended to exhibit agentic animism. Through a discussion of the differences between young children’s and older participants’ animism, we found that it is necessary to further study this topic to create robots that are better suited to people’s needs.
Keywords: Animism; Human-robot interaction; Mentalizing